Molecular cloning and functional characterization of the promoter of a novel Aspergillus flavus inducible gene (AhOMT1) from peanut - Zhuang, Yuhui; Sharif, Yasir; Zeng, Xiaohong; Chen, Suzheng; Chen, Hua; Zhuang, Chunhong; Deng, Ye; Ruan, Miaohong; Chen, Shuanglong; Weijian, Zhuang (Frontiers in Plant Science, 2023)
Peanut is an important oil and food legume crop grown in more than one hundred countries. Unfortunately, peanut yield and quality are often impaired by different pathogens and diseases, especially aflatoxins affecting human health. Aspergillus flavus is the main aflatoxin-producing pathogen, and A. flavus inducible genes provide good management options by exploiting the promoters of these genes. This study reported a novel A. flavus inducible promoter of the O-methyltransferase gene (AhOMT1) from peanut. The AhOMT1 was isolated by microarray analysis as the highest inducible by A. flavus. The AhOMT1 was characterized by genome-wide in silico assay, RNAseq, and qRT-PCR, revealing no expression in all tissues, weak or no response to low temperature, drought, hormones, Ca2+, and bacterium stresses, but highly induced by A. flavus infection. It contains four exons encoding 297 aa predicted to transfer the methyl group of S-adenosyl-L-methionine (SAM), leading to the methyl ether variants of numerous different substances. The promoter contains different cis-elements responsible for its expression characteristics. The AhOMT1P fussed with the GUS gene was introduced into Arabidopsis to generate homozygous transgenic lines. Functional characterization of AhOMT1P in transgenic Arabidopsis plants demonstrated its inducible behavior only under A. flavus infection. Transgenic Arabidopsis plants did not show GUS expression in any organs without inoculation with A. flavus spores. However, an increase in GUS activity after inoculation and increased expression was still maintained after 48 hours of infection. Expression of the AhOMT1 promoter was not enhanced in response to different plant hormones. The results provided the significance of this promoter for aflatoxins management by driving a resistance gene in A. flavus inducible manner.